New Challenges, Old Hatred: The Role of Super-diversity, Immigration, and Political Polarization in the Rise of Antisemitism in Contemporary Canada - Hollinger, Megan S. (Women in Judaism, 2023)
This paper examines the rise of antisemitism in contemporary Canada and explores some emerging social trends that may exacerbate and enable it. Specifically, the rise and maintenance of antisemitism in Canada may be, in part, due to the multifaceted diversification of the West known as super-diversity, as well as increasing political polarization. By examining super-diversity and its implications, this paper explores the connections between immigration and diversification, the growth of political polarization, and the rise in antisemitism across Canada. This paper argues how the aforementioned social trends may lead to the existence of more antisemitic manifestations and motivations in Canada. Of particular concern is the importation of certain anti-Israel and anti-Zionist biases found within populations arriving in Canada and coming from parts of the world where tensions with Israel are present. Additionally, political polarization heightens intergroup tensions in Canada and may foster a broader atmosphere of prejudice.